A retrospective study on beta-blocker use and outcomes in hematopoietic stem cell transplant patients - Matthew A. Bergens; John T. Bokman; Ernaya J. Johnson; Matthew L. Braun; Yan Li; Amy T. Bush; Lauren Hill; Jolien Van Opstal; Alessandro Racioppi; Rebecca Fan; Sejal Kaushik; Edwin Alyea; et al. (PeerJ)
Recent studies have linked beta-blocker (BB) use in critical care settings with improved survival outcomes, potentially due to beta-adrenergic receptor (β-AR) blockade and associated anti-inflammatory effects. Given the immune system’s role in the development of graft-versus-host disease (GVHD)—a major complication of allogeneic hematopoietic stem cell transplant (allo-HCT)—we conducted a single-center retrospective review to assess the impact of BB use on acute GVHD (aGVHD) and other survival outcomes in patients undergoing their first allo-HCT. We analyzed 10 years of data (January 2010 to May 2020), including 105 patients who received a BB for more than four days before and after HCT, and 669 control patients who did not receive a BB. Patients on BBs had a lower incidence of aGVHD (55.2% vs. 65.8%, p = 0.036); however, this difference was not statistically significant in multivariate analysis (p = 0.150). When stratified by BB mechanism, outcomes varied: non-selective BBs were associated with lower post-HCT weight (p = 0.034), and vasodilating BBs showed a borderline reduction in length of stay (LOS) (p = 0.054). While our findings confirm the pharmacological safety of BBs in this population, they do not support their routine use for modifying allo-HCT outcomes. Future prospective studies with larger cohorts are needed to further explore the role of BBs in peri-HCT management and to clarify their clinical implications and therapeutic potential.